The Effectiveness of Using Group Guidance Services with the Ability Potential Response (APR) Technique to Reduce Academic Burnout in Final Year Students - Umikalsum Arfa; Rita Samad; Dyla Fajhriani Nasrul; Nurul Jariah; A. Agustan Arifin (Universitas PGRI Yogyakarta, 2026)
Students often experience boredom and stress. Students experience this because they are working on their thesis and lecture assignments, which is known as academic burnout. Academic burnout can cause psychological problems for students. To reduce this problem, you can use group guidance services using the ability potential response technique, also known as APR. Ability potential response, is a technique in group guidance that focuses on counselors verbally recognizing students' ability to be independent in carrying out various activities. This study aims to determine and describe the effectiveness of group guidance services using APR techniques in reducing student burnout. The research method is a quantitative approach with a quantitative research design, an experimental method, and quantitative data analysis using SPSS version 20 with the Kruskal-Wallis Significance Rank Test, employing purposive sampling with a research sample of 20 students. This study demonstrates the impact of group guidance services that use APR techniques on reducing student burnout. Based on the study's results, group guidance using this ability potential response technique was effectivei to reducing students' academic burnout. Keywords: academic burnout, ability, potential response techniques, group guidance